A solar powered TEC driven picnic box - Su, Kelvin Yong Xun. (2009)
The project deals with the development of cooling system for a picnic box using thermoelectric technology. It also includes study on the thermoelectric technology, solar powered technology and the design process for integrating the 2 technology into the cooling system. A prototype of the cooling system is fabricated and experiment is conducted on the prototype to analyze the performance of the cooling system. The cooling system consists of heat sinks, cooling plate, thermoelectric module, a fan and a solar panel. The solar panel converts solar energy into electricity by the photovoltaic effect, which is use to charge up the battery When the electrical voltage from the battery is applied to the thermoelectric module, it will create a temperature difference across the thermoelectric module. This phenomenon, known as the Peltier effect, is used to utilize electricity to pump heat. In the cooling process, the heat dissipated by the 6 cans of coke is pump out to the heat sink by the thermoelectric module. The heat is transferred through the components by the means of conduction. The air volume flow rate from the fan introduced a forced convection heat dissipation effect. Therefore the heat collected at the heat sink is exhausted to the ambient by means of forced convection. Experimental investigation and relevant analysis on a solar powered, thermoelectric picnic box has been conducted. To make the device portable, daytime use and night time use of the picnic are treated in different ways. Solar cells are applied to power the refrigerator in the day. Storage battery, assisted by an a.c. converter, is used to provide electric energy in the night and in cloudy or rainy days. Experiment results demonstrate that the unit can maintain the temperature in the refrigerator at 8–17 °C, It is expected that the refrigerator would be potential for cold storage of vaccine, foodstuffs and drink in remote area, or outdoor applications where electric power supply is absent